Dermatology Quality of Life and Depressıon Anxiety and Stress-42 Scale in Scabies Patients - Serap Karadoğan; Berna Ulgen Altay (Mattioli1885, 2024)
Introduction: Scabies is a pruritic skin infestation with a globally increasing prevalance. Sleep problems, dispaired social and personal interactions, mainly due to itching, have been reported. Objectives: We aimed to determine the influence of scabies on quality of life and psychosocial health using Dermatology Quality of Life Index (DQOL) and Depression Anxiety and Stress-42 (DASS-42) Scale and analyse whether there is a correlation between the two scales and any sociodemographic and clinical characteristics. Methods: Scabies patients (>16 years) who presented to our Outpatient Clinics were enrolled. Age, gender, occupation, marital status and education level and clinical features were recorded. DQOL Index and DASS-42 Scale were used. Possible influence of demographic and clinical characteristics on total scores were analysed. The Spearman coefficient analysis was performed to determine whether there is a correlation between these scores. Results: Of 92 patients (mean age:37.76±15.355, Female/Male: 1.09/1) 63% were married and 35.9% were high-school graduates; 27.2% and 23.9% were housewives and officer-proffesionals. Disease was generalized in 57.6% and duration of disease was mostly <4 weeks. Mean DQOL and DASS-42 scores were 13,16±7,638 and 42.10±30.644, respectively. Symptoms/feelings were affected predominantly. DQOL was affected 'severely' in 41.3% of patients. Conclusions: Impairment of DQOL is a significant predictive parameter for higher DASS levels. Scabies is not only associated with impairment in DQOL but may also lead to psychosocial problems. All scabies patients should be evalauted and consulted -if needed- for possible problems of psychosocial status including depression, anxiety and stress as well as clinical symptoms and secondary complications.